(untitled) (REMUNOM, 2025)
As urban changes occur, we seek sustainable alternatives to plant, reuse and preserve, thus contributing to a balanced environment. The use of organic fertilizers has been a great alternative. They are classified according to several criteria, classified as: mineral or inorganic, organic and organo-mineral. Therefore, in this article we present the importance of implementing organic fertilizers in our daily lives, highlighting the notoriety of their use and practicality. Such practices, when incremented, are visibly notable, used correctly, from quality to productivity. Furthermore, when we observe the stages of evolution of the use of organic fertilizers, we can mirror them in the present day, and highlight the qualities, such as more fertile soils, healthier foods, the leaching process without environmental damage, among many other peculiarities. Normally, fertilization requires several nutrients, with the intention that they are applied together in the same operation. Simple fertilizers are mixed, making a mineral compound. It is important to know which nutrients each compound will bring to the fertilizer, in order to have a precise fertilizer. However, there is still a lot of misinformation today regarding the use of organic fertilizers, a subject that is still little explored and tends to be underused, as it is more suitable for small crops, due to the demand for substances to form it. Therefore, with this article we want to simplify and expand knowledge on this subject, providing data and information that seek to facilitate this learning. Therefore, with so many significant results, it is of utmost importance that we work with organic fertilizers, as with them, we will get as close as possible to sustainable agriculture and a balanced ecosystem. Keywords: sustainability, notoriety, qualities, fertility.